The thermoluminescence response of doped silicon dioxide optical fibres to ionizing radiation - Hashim, Suhairul (2009)
This work concerns the suitability of doped SiO2 fibres as ionizing radiation dosimeters. The physical characters of the amorphous medium are discussed, as is the origin of the thermoluminescence (TL) signal and desirable characteristics of such a dosimeter. Facilities supporting characterization of the fibres are outlined, including an ion beam facility used for Particle Induced X-ray Emission and Rutherford Back Scattering analysis used to localize and determine the concentration of Ge and Al dopants. The dosimetric capabilities of Ge-, Al-, O2-doped and pure SiO2 optical fibres were investigated for low-energy X-rays, megavoltage photons, ?-rays, accelerated electrons and accelerated protons, ?-particles and fast neutrons. For Ge- and Al-doped fibres, linearity of dose responses were observed over useful radiotherapeutic dose range for 6 MV photons and 6 to 12 MeV electrons. TLD-100 provides a TL yield about 10 times that of Ge-doped fibre and about 30 times that of Al-doped fibres. The same order of sensitivity is displayed using a ?-ray source. Linear dose response was also observed for 2.5 MeV protons irradiation. For ?-particles the Bragg peak was localised to 4.5 cm in air from the point of emission. Strong TL response to fast neutrons was also found for Ge-doped fibres but was negligble for Al-doped fibres. These findings are supported by Monte Carlo simulations. Zeff of between 11.9-13.4 and 11.7-13.7 were found for Ge- and Al-doped fibres respectively. The minimum detectable dose for Ge-, Al-doped fibres and TLD-100 chips were observed to be in the range of 30-50µGy, 800-1400µGy and 3-5 µGy respectively, for 6 MV photons, and 6-, 9- and 12 MeV electron irradiation. The peak of the glow curve is between 210oC to 240oC; the broad glow curve is characteristic of amorphous media. With oxygen forming additional defect centres in fibres, ion-implantation was used to dope pure silica with O2 defects, implanting to the depth of 160 nm. The results show promising sensitivity on first use, although subsequent annealing leads to the loss of practically all of the dopants